Caffeine Potentiates Ethanol-Induced Neurotoxicity Through mTOR/p70S6K/4E-BP1 Inhibition in SH-SY5Y Cells. (March 2020) - Sangaunchom, Pongsak; Dharmasaroja, Permphan
Caffeine is a popular psychostimulant, which is frequently consumed with ethanol. However, the effects of caffeine on neuronal cells constantly exposed to ethanol have not been investigated. Apoptosis and oxidative stress occurring in ethanol-induced neurotoxicity were previously associated with decreased phosphorylation of the mTOR/p70S6K/4E-BP1 signaling proteins. Evidence also suggested that caffeine inhibits the mTOR pathway. In this study, human SH-SY5Y neuroblastoma cells were exposed to caffeine after pretreatment for 24 hours with ethanol. Results indicated that both ethanol and caffeine caused neuronal cell death in a dose- and time-dependent manner. Exposure to 20-mM caffeine for 24 hours magnified reduced cell viability and enhanced apoptotic cell death induced by 200 mM of ethanol pretreatment. The phosphorylation of mTOR, p70S6K, and 4E-BP1 markedly decreased in cells exposed to caffeine after ethanol pretreatment, associated with a decrease of the mitochondrial membrane potential (ΔΨm). These findings suggested that caffeine treatment after neuronal cells were exposed to ethanol resulted in marked cell damages, mediated through enhanced inhibition of mTOR/p70S6K/4E-BP1 signaling leading to impaired ΔΨm and, eventually, apoptotic cell death.